Subjects-in-Process/ on-Trial: The Construction of Teacher Subjects in an Early Field Experience Course - Bach, Jacqueline (Paideusis, 2008)
Increased standardization of teacher education programs urges a reconsideration of how pre-service teacher identities are constructed/being constructed and evaluated. The purpose of my study was to examine the writings of pre-service teachers enrolled in an early field experiences course in order to identify moments in which they interacted, negotiated, and subverted the teacher-making process, which they officially enter during the semester they take this course. I approach this question from a philosophical viewpoint, and I use the theories of French post-structuralist, Julia Kristeva. My analysis of pre-service teachers enrolled in an early field experience course illustrates how their language disrupts the standardized language and expectations of a teacher education program.